Potentially inappropriate medications used by the elderly: Prevalence and risk factors in Brazilian care homes - Vieira de Lima, Thaís Jaqueline [UNESP]; Garbin, Clea Adas Saliba [UNESP]; Garbin, Artênio José Ísper [UNESP]; Sumida, Doris Hissako [UNESP]; Saliba, Orlando [UNESP] (Springer Nature, 2013)
Abstract. Background: The use of potentially inappropriate medications (PIM) among the elderly is a serious public health problem because it is intrinsically linked to increased morbidity and mortality, causing high costs to public health systems. This study's objective was to verify the prevalence of and the factors associated with the use of PIMs by elderly Brazilians in institutional settings. Methods. We performed a transversal study, by consulting the case files of elderly people living in Long Term Care for the Elderly (LTC) in towns in the State of São Paulo, Brazil, as well as structured interviews with the nurses responsible for them.We identified PIMs using the list of recently updated Beers criteria developed by a group of specialists from the American Geriatrics Society (AGS), who reviewed the criteria based on studies with high scientific evidence levels. We defined the factors studied to evaluate the association with PIM use prior to the statistical analyses, which were the chi-square test and multiple logistic regression. Results: Among the elderly who used drugs daily, 82.6% were taking at least one PIM, with antipsychotics (26.5%) and analgesics (15.1%) being the most commonly used. Out of all the medications used, 32.4% were PIMs, with 29.7% of these being PIMs that the elderly should avoid independent of their condition, 1.1% being inappropriate medication for older adults with certain illnesses or syndromes, and 1.6% being medications that older adults should use with caution. In the multivariate analysis, the factors associated with PIM use were: polypharmacy (p = 0.0187), cerebrovascular disease (p = 0.0036), psychiatric disorders (p < 0.0001) and dependency (p = 0.0404). Conclusions: The results of this study showed a high prevalence of PIM use in institutionalized elderly Brazilian patients. and the associated factors were polypharmacy, psychiatric disorders, cerebrovascular diseases and dependency. © 2013 Lima et al.; licensee BioMed Central Ltd.
Keywords: Aged; Drug utilization; Inappropriate prescribing